THE SYSTEMIC CONCEPT IN IMPROVEMENT QUALITY OF LIFE TO STUDENTS - Andreea - Gabriela Lazăr (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
System theory is described as an interdisciplinary epistemological model in which systems are used to describe and explain a varying phenomen with degrees of complexity. The system is a lot of elements between, which there are in relationships or non-interrelated relationships that interact in order to achieve a common goal. The concept of systems theory is used in various scientific disciplines, even in Physical Education and Sports. The theory of systems is the superior knowledge of objects possessing the property of completeness, a set of entities compacts that constitute themselves as the quality of life discussed in this article from the perspective of a complex system. Some elements that condition the quality of life and which can be addressed from the perspective of the general theory of systems are: the intersystem relationships between the health system and the education system: physical, mental and social well-being as subsystems of the quality of life; health as an element of physical well-being; physical condition as an element of health; exercise as a necessary condition for a good health; exercise as a means of physical education lesson; exercises practiced in physical education lessons that can lead to an improvement in the quality of life.